Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations of starchy foods, such as bread and potatoes. The sensible course is to drink sufficient at meals to help mastication and to make the meal enjoyable, and to drink more copiously in between to quench thirst. The glass of water on rising will clean the stomach and help the bowels to move the accumulated contents out of the body, and the bed-time glass will help internal cleanliness during the hours of sleep. The presence of roughage (fibrous material) in vegetables keeps the contents of bowel moving — that is one of its valuable properties. Milk, for instance, has no roughage, and so is liable to cause constipation, which is a polite name for stoppage of the body-drains. Every human being — except a baby — needs to eat some indigestible material as a stimulant of the larger bowel to healthy activity. For most people this is found in the fibres of green food and fruits. Rich foods, riding about in cars and trams and buses, sitting about in easy chairs (and sheer laziness!) are apt to bring about an inactive bowel, and microbes seize upon the stagnant food and manufacture poisons which are absorbed into the blood stream. The result of this poisoning is seen on the skin as blotches, pimples and rashes, and a general upset of the body. To such poisoning half the ills that girls suffer from is due — headache, liability to "colds," tonsillitis, influenza, lumbago, "bilious attacks" and the blues! Keeping the inside clean will save many a doctor's bill; and the best way to do this by natural means and not by chemical means — drugs — is by eating foods that keep themselves on the move, such as oatmeal, green vegetables, salads, wholemeal bread and fruits; specially figs, dates and prunes. These foods will give the large bowel aid from within, and exercise will give it aid from without. Good and regular habits are essential, such as 22 177/5/8/4